2002
DOI: 10.1017/s0317167100002183
|View full text |Cite
|
Sign up to set email alerts
|

Auditing Carotid Endarterectomy: A Regional Experience

Abstract: 326Studies and commentaries from the 1980s expressing concern about the efficacy, appropriateness, and complications of carotid endarterectomy (CEA), 1 -8 were followed by a series of multicenter randomized controlled trials comparing CEA to medical treatment alone. Reported throughout the 1990s, these studies validated the use of CEAunder certain circumstances, [9][10][11][12][13][14][15] and led to a rapid and large resurgence in the use of CEA in A B S T R A C T: Background: Proof from randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Inappropriate surgery could be curtailed by applying appropriateness ratings before surgery 19 or by consistently educating surgeons with feedback of their own results. 20 In addition to the patient factors used to determine appropriateness, surgical skill is of critical importance, and its assessment requires outcome measurements in all cases. 20 This study allows a deeper understanding of the factors contributing to marked practice variation across western Canada than was previously described with the use of an administrative database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate surgery could be curtailed by applying appropriateness ratings before surgery 19 or by consistently educating surgeons with feedback of their own results. 20 In addition to the patient factors used to determine appropriateness, surgical skill is of critical importance, and its assessment requires outcome measurements in all cases. 20 This study allows a deeper understanding of the factors contributing to marked practice variation across western Canada than was previously described with the use of an administrative database.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition to the patient factors used to determine appropriateness, surgical skill is of critical importance, and its assessment requires outcome measurements in all cases. 20 This study allows a deeper understanding of the factors contributing to marked practice variation across western Canada than was previously described with the use of an administrative database. 21 CE volume had a clear inverse relation with the rate of appropriate CE, both high-volume surgeons and high-volume hospitals having lower CE appropriateness rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although this better selection of surgical candidates is admirable, one must also be aware that previous studies have reported that low-volume surgeons in low-volume hospitals have more perioperative complications of stroke and death than do high-volume surgeons in institutions making extensive use of CE. 7,8 Although the current study does not provide details of hospital complication rates, one can expect that these rates will be higher in low-volume centres. It is not sufficient for CE to be done for appropriate reasons only.…”
mentioning
confidence: 88%
“…Only one study had a small (7%) proportion of patients reviewed by an independent neurologist postprocedure. 34 Inclusion criteria ranged from "no documented history of ipsilateral cerebral ischemia" 33 to "no ipsilateral hemispheric symptoms in the past 6 months" 38 and in 6 cases were not stated. Exclusion criteria were variable.…”
Section: -45mentioning
confidence: 99%